Electrical Accidents In The Mining Industry, 1990-1999 (a667b09a-202f-425d-9b08-95e0dee3b098) - J. C. Cawley (Society for Mining, Metallurgy & Exploration, 2002)
This National Institute for Occupational Safety and Health study was conducted to focus future research on the most significant electrical problems in the mining industry. Data from 1,926 mine electrical accidents (including 75 fatalities) that occurred between 1990 and 1999 were studied. Coal and metal-nonmetal operator- and contractor-reported data are presented. All data used in this analysis were MSHA closeout data, except 1999, which were preliminary data. Electricity was the 4th leading cause of death reported in mining despite being the 14th leading cause of injuries. Electrical shock, not electrical burns, caused 70 of the 75 electrical fatalities reported. About one-half of mine electrical accidents and fatalities occurred during electrical maintenance. Suggestions for mitigating electrical hazards are proposed.